The impact of metabolic stressors on mitochondrial homeostasis in a renal epithelial cell model of methylmalonic aciduria - Schumann, Anke; Brutsche, Marion; Havermans, Monique; Grünert, Sarah; Kölker, Stefan; Groß, Olaf; Hannibal, Luciana; Spiekerkötter, Ute (Scientific reports, 2023)
Methylmalonic aciduria (MMA-uria) is caused by deficiency of the mitochondrial enzyme methylmalonyl-CoA mutase (MUT). MUT deficiency hampers energy generation from specific amino acids, odd-chain fatty acids and cholesterol. Chronic kidney disease (CKD) is a well-known long-term complication. We exposed human renal epithelial cells from healthy controls and MMA-uria patients to different culture conditions (normal treatment (NT), high protein (HP) and isoleucine/valine (I/V)) to test the effect of metabolic stressors on renal mitochondrial energy metabolism. Creatinine levels were increased and antioxidant stress defense was severely comprised in MMA-uria cells. Alterations in mitochondrial homeostasis were observed. Changes in tricarboxylic acid cycle metabolites and impaired energy generation from fatty acid oxidation were detected. Methylcitrate as potentially toxic, disease-specific metabolite was increased by HP and I/V load. Mitophagy was disabled in MMA-uria cells, while autophagy was highly active particularly under HP and I/V conditions. Mitochondrial dynamics were shifted towards fission. Sirtuin1, a stress-resistance protein, was down-regulated by HP and I/V exposure in MMA-uria cells. Taken together, both interventions aggravated metabolic fingerprints observed in MMA-uria cells at baseline. The results point to protein toxicity in MMA-uria and lead to a better understanding, how the accumulating, potentially toxic organic acids might trigger CKD.